2011
DOI: 10.1007/s12032-011-9904-1
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid inhibits proliferation and impairs migration and invasion through downregulating VEGF and MMPs expression in human nasopharyngeal carcinoma cells

Abstract: To demonstrate the effect of zoledronic acid in proliferation, invasion, and migration of human nasopharyngeal carcinoma cell HNE-1 and explore the potential role of VEGF, MMP-2, and MMP-9 proteins in vitro. Human nasopharyngeal carcinoma cell HNE-1 was exposed to various concentrations (0-40 μmol/l) of zoledronic acid. Zoledronic acid inhibited proliferation of HNE-1 cells though not in a dose-dependent manner. Zoledronic acid had exerted a dose-dependent effect on the migration and invasion of HNE-1 cells. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…Our previous study reported that ZOL may impair cancer cell migration and invasion via downregulating vascular endothelial growth factor and matrix metalloproteinase expression (28). Therefore, the aim of the present study was to examine whether this anti-metastatic effect could be augmented by co-treatment with ZOL plus IR.…”
Section: Zol Plus Ir Results In Significant Anti-metastatic Effects Omentioning
confidence: 90%
“…Our previous study reported that ZOL may impair cancer cell migration and invasion via downregulating vascular endothelial growth factor and matrix metalloproteinase expression (28). Therefore, the aim of the present study was to examine whether this anti-metastatic effect could be augmented by co-treatment with ZOL plus IR.…”
Section: Zol Plus Ir Results In Significant Anti-metastatic Effects Omentioning
confidence: 90%
“…The recent use of bisphosphonates was associated with decreased MMP activation [20][21][22]. In addition, bisphosphonates treatment in patients with several types of cancer decreased serum lipid hydroperoxide levels and increased serum glutathione peroxidase levels [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also showed that doxycycline inhibited activity of gelatinases and diminished tumor growth, invasion and metastasis in osteosarcoma, and lung, ovarian, cervical and oral cancer cell lines [39][40][41][42]. Similarly, zoledronate, which is nitrogen-containing bisphosphonate, exerts antitumoral effects by suppressing MMP expression and/or activity in various cancers [43,44]. Recently, we have also reported that zoledronate downregulated MMP-2 and -9 expression and activities in PC3 prostate cancer cells [45].…”
Section: Discussionmentioning
confidence: 89%